Urinary schistosomiasis in Guinea Bissau - Botelho, M.C. (2015)
Urogenital schistosomiasis due to Schistosoma (S.) haematobium is among the most prevalent parasitoses in sub-Saharan Africa. The pathology is characterized by serious and irreversible lesions in the urogenital tract induced by chronic infection with the parasite that can eventually lead to renal failure due to hydronephrosis and to squamous cell carcinoma of the bladder. Considering the frequency and severe morbidity observed already in young children, the purpose of this pilot study was to assess the prevalence and morbidity of S. haematobium infection in Guinea Bissau. A baseline survey was conducted during September 2011. A randomly selected sample of 90 children aged 6–15 years old was included in this study. Prevalence of S. haematobium infection was 20% (18/90). It was higher in older children (median age in years: 15.4 2.71 vs. 9.3 2.22; P < 0.001), a significant gender difference in prevalence and intensity was not found. The predominant symptom was haematuria (87.1%), this symptom being strongly associated with S. haematobium infection (P < 0.01). Anthropometric examination revealed that growth in infected boys was impaired as compared to non-infected boys (median height in cm: 123.3 21.07 vs. 134.71 15.1) (P < 0.05). To our knowledge this is the first epidemiologic report of S. haematobium infection in Guinea Bissau. Considering the high prevalence of S. haematobium infections in Guinea Bissau and the long-term risks, including renal failure and bladder cancer, our results indicate that this population should be targeted for follow-up and implementation of measures for treatment and control of schistosomiasis.